NARRATING REPAIR: TESTIMONIAL JUSTICE AND IDIOMATIC HEALING AS ETHICAL INTERVENTION IN CLIMATE-AFFECTED COMMUNITIES - Francis Paul Kerre, (PEOPLE: International Journal of Social Sciences, 2025)
This paper examines testimonial justice and idiomatic healing as sociological responses to climate injustice and symbolic rupture. In communities facing environmental degradation and gendered displacement, trauma manifests not only physically but narratively. The research aims to explore how narrative practices—rooted in African idioms, ritual storytelling, and testimonial pedagogy—can serve as ethical interventions that foster communal repair and climate resilience. Methodologically, the study draws on participatory fieldwork in peri-urban Kenya, engaging elders, youth, and displaced families in dialogic rituals of memory and healing. Comparative reflections with Eurasian traditions of ethics and symbolic governance enrich the analysis. Findings reveal that narrative acts—when culturally grounded—enable communities to reconstitute dignity, agency, and ecological consciousness in the face of epistemic violence. The paper contributes to interdisciplinary debates on media ethics, cultural rehabilitation, and climate justice by proposing a framework where symbolic repair becomes central to sociological intervention. Future scope includes scaling idiomatic healing models across climate-affected regions and integrating testimonial pedagogy into policy and education platforms.